Can Al-Faruqi’s Islamization Deals with Islamic Economics? Revisiting Al-Faruqi’s Islamization of Economics - Ma'ruf, Aminudin; Kurniawan, Adityo Wiwit; Fatoni, Muhammad Iqbal; Alam, Shahbaz; Hakim, Lukmanul (Universitas Darussalam Gontor, 2023)
This study attempts to examine al-Faruqi’s Islamization of knowledge concept in relation to Islamic economic studies. The paper employs a qualitative research method with the library and literature study approach. The study finds that al-Faruqi’s concept of Islamization of knowledge has put the fundamental principles of Islamization of economics. The concept covers the steps of mastery of the modern discipline, disciplinary survey, and mastery of the Islamic heritage. The study henceforth urges stakeholders of Islamic economic studies to consider al-Faruqi’s Islamization concept in their development of Islamic economic sciences. Furthermore, the paper encourages future research on exploring the application of al-Faruqi’s Islamization of knowledge concept driving the future of Islamic studies.